THE ROLE OF UNITDIKYASA SATLANTAS POLRES SUKABUMI KOTA IN THE PREVENTION OF TRAFFIC VIOLATIONS DURING THE COVID-19 PANDEMIC - Alfin Muhammad Alfin Ilham (Advances in Police Science Research Journal, 2019)
The growth in the number of motor vehicles is always followed by traffic problems. Traffic problems such as traffic jams, violations, and accidents. Traffic violations have the potential to cause accidents and traffic jams in the jurisdiction of Polres Sukabumi Kota. Unitdikyasa Satlantas Polres Sukabumi Kota has an important role in the prevention of traffic violations through the role performed by Unitdikyasa such as Dikmaslantas, judicial operations, and Friday blessings. In accordance with this, the author took several formulations of problems, namely how the situation and traffic conditions in the jurisdiction of Polres Sukabumi Kota during the Covid-19 pandemic, how the role of Unitdikyasa Satlantas Polres Sukabumi Kota in the prevention of traffic violations during the Covid-19 pandemic, and factors that affect the role of Unitdikyasa Satlantas Sukabumi Kota Police in the prevention of traffic violations during the Covid-19 pandemic. This research was conducted in the jusrisdiction of Polres Sukabumi Kota using several theories and concepts.The theory used is communication theory, management theory, and behavioristic learning theory and the research method used is in the form of field research (Field Research). Based on the results of the study there are answers or formulation of problems related to the situation and traffic conditions in Sukabumi City is always crowded and crowded so that it often causes traffic congestion, related to the role of Unitdikyasa, namely the implementation of the Dikmaslantas program, yustisi operations, and Friday blessings, but still constrained, related to factors that affect internal and external factors. Recommendations given in accordance with the conclusion, in the form of theoretical recommendations and practical recommendations. Theoretical recommendations are that programs implemented by Unitdikyasa have a very important role in preventing traffic violations during the Covid-19 pandemic. The practical recommendation is that the National Police can use the Unitdikyasa program to increase public awareness and participation in traffic order.